2015
DOI: 10.2147/oaip.s84053
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase activities in the midgut of Helicoverpa armigera larvae: identification and biochemical properties of a manganese superoxide dismutase

Abstract: Insects possess a complex network of enzymatic antioxidant systems protecting against reactive oxygen species generated during stress. Superoxide dismutases (SODs) are vital antioxidant enzymes converting superoxide into oxygen and hydrogen peroxide. Helicoverpa armigera is a polyphagous insect and has developed resistance to various phytochemicals and pesticides. Although SODs are studied in several insect species, their characterization has been reported in only a few insect species. Here, we attempted to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The study demonstrated significant antioxidant activity by performing different assays namely SOD, DPPH, and GST in the hydro-alcoholic extract of C. chinensis . Superoxide dismutase (SOD) is one of the key enzymes of insect antioxidant system 25 . The importance of SOD in therapeutic potential and physiological have already been mentioned in several reports.…”
Section: Resultsmentioning
confidence: 99%
“…The study demonstrated significant antioxidant activity by performing different assays namely SOD, DPPH, and GST in the hydro-alcoholic extract of C. chinensis . Superoxide dismutase (SOD) is one of the key enzymes of insect antioxidant system 25 . The importance of SOD in therapeutic potential and physiological have already been mentioned in several reports.…”
Section: Resultsmentioning
confidence: 99%
“…However, this production could be degraded by superoxide dismutase [Cu-Zn]. Superoxide dismutases are key antioxidant enzymes converting superoxide into oxygen and hydrogen peroxide ( 50 ). We found that superoxide dismutase was significantly upregulated after leafhopper exposure to MRFV at 4 h, suggesting that ROS production may be disarmed by 4 h after virus entrance vector.…”
Section: Discussionmentioning
confidence: 99%
“…ROS accumulation activates the mosquito Toll immune pathway, resulting in the production of AMPs (Pan et al, 2012). Possibly as a result of this ROS amount, Cu-Zn superoxide dismutase (SOD) proteins (AAEL019937 and AAEL025388) were upregulated comparing WZ with W, Z and A. SODs are an important antioxidant enzymes that convert superoxide into oxygen and hydrogen peroxide (Park et al, 2012;Lomate et al, 2015) and it is also related to protecting insects' ovaries during diapauses (Sim & Denlinger, 2011). Besides ROS-mediated immune response, a DEAD box ATP-dependent RNA helicase (AAEL004978) was upregulated in coinfection.…”
Section: )mentioning
confidence: 99%